Mutation rate of 12 X-STRs from investigator Argus X-12 kit in Argentine population. (December 2017) - García, M.G.; Gusmão, L.; Catanesi, C.I.; Penacino, G.A.; Pinto, N.
Abstract: The analysis of X-chromosomal markers can be important in different situations where the application of autosomal and Y- chromosomal STR markers are not sufficient to solve the cases. Currently, the Argentine population lacks a representative database on X-chromosomal markers, regarding allele and/or haplotype frequencies, and mutation rates. The absence of this information represents an important limitation for their routine use in laboratories, preventing the achievement of a quantitative, statistically supported evaluation. In order to estimate mutation rates for the twelve X-chromosomal markers included in the Argus X-12 kit, 345 father-daughter duos were genotyped. The samples were selected from all provinces of Argentina and the biological relationship of paternity was previously confirmed by the analysis of autosomal STR markers for all duos, for which likelihood ratios higher than 10 6 were achieved. A total of 21 mutations over 4140 allelic transmissions were observed at DXS7132, DXS10134, DXS10079, DXS10146, DXS10101, DXS10103, DXS10074, DXS10148 and DXS10135 loci. The overall X-STRmutation rate observed was 5.1 × 10 −3 (95% CI, 3.1 × 10 −3 –7.7 × 10 −3 ) and all the genotypic configurations were explainable by the gain or loss of a single repeat. Finally, it should be noted that the overall mutation rate observed in this work resulted higher in comparison with some other reports, likely due to only father-daughter duos had been considered. Indeed, these findings are in agreement with previous works suggesting higher mutation rates for males, due to the higher number of germ-line divisions they experience.